Pengaruh Motivasi dan Model Pembelajaran Creative Problem Solving Terhadap Kemampuan Berpikir Kreatif Matematis Siswa : Systematic Literature Review - Fayesa, Intan; Garawati, Ratna Ayu; Hamidah, Ida (STAI Al-Bahjah, 2023)
Mathematics is a subject that supports students' creativity in mathematical thinking. Because mathematics requires students to be able to think creatively and critically, This research aims to conduct a study using the literature review method related to the influence of motivation and the CPS (Creative problem solving) learning model on students' mathematical and creative thinking abilities. The research method was carried out using a qualitative library research approach and the SLR (systematic literature review) data collection method for all articles related to the object of this research, including 30 national and international journal articles obtained from Google Scholar. From this research, it was found that motivation and creative problem-solving learning models influence students' creative thinking abilities. Creative teachers, learning media, class atmosphere, and appropriate learning methods and models support increasing students' creative thinking abilities.